The Collaboration Learning Interactive Multimedia using Traditional Games "Benteng-Bentengan" in Geography Subject for High Schools - Prastiyono, Hendri; Amin, Saiful; Fadirubun, Fahmi Fahrudin; Sitohang, Lidya Lestari (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
This study aims to develop a collaboration learning with interactive multimedia using traditional games "Benteng-Bentengan" in Geography Subject for high school. The application of the traditional games "Benteng" has been modified and adapted to the characteristics of the material. The design of this study used the Borg and Gall model which was modified into six, namely (1) needs analysis, (2) product development, (3) product revision, (4) product testing, (5) designing and (6) carrying out evaluation. This development research uses the validity test of learning, media and material experts. The study was conducted on 72 students of class XII IPS SMA Wachid Hasyim 2 Taman. The results of the questionnaire showed that the collaboration of interactive multimedia learning and the traditional games "Benteng" gave positive results with 94% or 34 students stating that collaboration is a fun, recreational, educative learning and faster understanding of the material. Based on the results of the competency test in the experimental class, an average of 84 was obtained with a gain score of 19 point. Thus, the collaboration of interactive learning multimedia and traditional games "Benteng-Bentengan", is able to effectively improve the learning outcomes of experimental class students. The results of this development and research are able to create a learning climate for millennial students to become agents of change in the future, especially the development of learning methods in the educational community.